Perioperative sildenafil citrate administration in hepatectomy: a study protocol of randomized controlled trial - Qisheng Chen; Shixuan Peng; Yingying Zhou; Shuzhai Li; Feng Xu; Yi Yu; Pan Wang; Xinran Peng; Chunbo Zhao; Aowen Xie; Zhiming Zhang (Trials)
Abstract Background Intraoperative blood loss (IBL) is the major concern in hepatectomy, which was closely relating to the central venous pressure (CVP). The controlled low central venous pressure (CLCVP) technique is moderately required for minimizing hemorrhage during hepatectomy nowadays. Nevertheless, an excessive reduction in CVP might give rise to the jeopardy of inadequate perfusion of vital organs. Sildenafil, being a first-line pharmaceutical for treating pulmonary hypertension, its mechanism of action lies in diminishing pulmonary vascular resistance (PVR) by dilating pulmonary arteries, and thereby alleviating the afterload of the right ventricle. We initially postulate that administration of sildenafil citrate in combination with intermittent Pringle’s maneuver (IPM) can exert a notable impact in efficaciously reducing intraoperative blood loss (IBL), enhancing the surgical field of vision, and augmenting the safety of the operation. Methods This research constitutes a double-blind, randomized, controlled trial. All patients fulfilling the criteria for open or laparoscopic hepatectomy will be randomly allocated to the sildenafil (S) group and the placebo (C) group via the block randomization approach. All surgeons, anesthesiologists, and outcome assessors will remain oblivious to the patient’s group details. The primary outcome is the intraoperative blood loss (IBL). Secondary outcomes include the classification of the surgical field, the cumulative consumption of nitroglycerine, hemodynamic parameters, blood gas analysis, coagulation function (comprising thromboelastogram (TEG), activated partial thromboplastin time (APTT), and prothrombin time (PT)), intraoperative urine output, adverse events in the recovery room (hypotension, hypoxemia and hematuria), biochemical markers (total bilirubin, total albumin, alanine aminotransferase, aspartate aminotransferase, creatinine, urea nitrogen), complete blood count (Hb, Plt, and Hct), cardiac function (brain natriuretic peptide, creatine kinase isoenzyme, troponin), postoperative hospital stay and indwelling time of drainage tube, and postoperative complications. These parameters will be comprehensively compared and analyzed in-depth through appropriate statistical means. Discussion This trial evaluated the influence of administration of sildenafil citrate combined with IPM on IBL and surgical results during open or laparoscopic hepatectomy, as well as its safety and feasibility. It is expected to provide an innovative management optimization plan for reducing the bleeding in hepatectomy, and to provide empirical support for the potential value of sildenafil citrate or sildenafil-like drugs in improving the safety and quality of perioperative hepatectomy patients. Trial registration This trial was registered on June 25, 2024, in the US Clinical Trials Registry ( https://register.clinicaltrials.gov ), with the ClinicalTrial.gov Identifier: NCT06237751. The protocol version is V1.0 (20,231,114).